ANALISIS PENERAPAN ETIKA BISNIS ISLAM PEDAGANG DI PASAR PAMENANG KABUPATEN MERANGIN JAMBI - Mareta Elesia Putri; Agusriandi Agusriandi; Faturahman Faturahman (CV. Aksara Global Akademia, 2023)
A market is an area where goods are bought and sold with more than one seller, whether referred to as a shopping center, traditional market, shops, mall, trade center or other designations. Deviant behavior is often found in traditional markets. Therefore, Islamic business ethics plays a very important role in regulating the behavior of traders. Islamic business ethics are ethical norms based on the Qur'an and hadith that must be used as a reference by anyone in every business activity. The purpose of this study was to determine the understanding of the Islamic business ethics of traders in Pamenang Market, Merangin Regency, Jambi. In this study the method used was qualitative by checking the validity of the data using triangulation techniques and the method of collecting data using observation and interviews. The informants in this study were five traders and five buyers. Based on the results of this study indicate that some traders in Pamenang Market have understood Islamic business ethics but there are still some traders who do not understand it. However, the behavior of traders in Pamenang Market is generally good in carrying out the principles of Islamic business ethics that have been implemented, namely there are three, the principle of balance (Equilibrum), the principle of free will, and the principle of truth (Benevolence), although there are still two principles that have not been fully implemented, namely: the principle of unity (Tauhud) and the principle of responsibility (Responsibility). Where traders still prioritize profits but do not pay attention to the losses of the buyer.